Effects of heavy metals and chelants on phytoremediation capacity and on rhizobacterial communities of maize. (1st September 2016) - Vigliotta, Giovanni; Matrella, Simona; Cicatelli, Angela; Guarino, Francesco; Castiglione, Stefano
Abstract: Heavy metals (HMs) are one of the major ecological problem related to human activities. Phytoremediation is a promising "green technology" for soil and water reclamation, and it can be improved by means of the use of chelants. In the past particular attention was paid on the effects of HMs and/or chelants on plant health, but much less on their effects on rhizosphere communities. To shed light on the interaction among plant-HM-chelant-rhizobacterial community a pot experiment was set up. Maize plants were grown on uncontaminated, multi-metal (copper and zinc) contaminated and chelants artificially amended soils. A high concentration of HMs was detected in the different maize organs; chelants improved the accumulation capacity of the maize plants. The rhizosphere bacterial community isolated from control plants showed the largest biodiversity in terms of bacterial genera. However, the addition of HMs reduced the number of taxa to three: Bacillus, Lysinibacillus and Pseudomonas . The effects of HM treatment were counteracted by the addition of chelants in terms of the genetic biodiversity. Furthermore, several bacterial strains particularly resistant to HMs and chelants were isolated and selected. Our study suggests that the combined use of resistant bacteria and chelants could improve the phytoremediation capacity of maize. Highlights: Maize-DDK 743phyto-stabilizes and -extract copper and zinc. Cu and Zn strongly reduce rhizosphere bacteria biodiversity. Chelants (EDTA and EDDS) improve Zn and Cu phytoremediation of DDK 743. EDTA or EDDS counter act the negative effect of Cu and Zn on rhizosphere bacteria. Metals and chelants were used to select resistant rhizobacteria.